Macroeconomic Risk, Fiscal Policy Rules and Aggregate Volatility in Asymmetric Currency Unions: A Behavioral Perspective - Christian R. Proa\~no (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper studies the dynamics of macroeconomic risk, fiscal policy and the macroeconomy in a two-country monetary union framework, under the assumption that agents do not have rational expectations, but use heuristics to determine their consumption over time, as well as to assess macroeconomic risk. Further, the macroeconomic consequences of a divergence between the design of fiscal policy and the behavioral perception of macroeconomic risk by the financial markets are investigated using numerical simulations. Among other things, these simulations show that an extreme focus on debt stabilization can be counterproductive if the financial markets care more about other indicators, such as the country's output gap or external imbalances.
urn:nbn:de:101:1-2014031112303
Keywords: 330; Behavioral macroeconomics; macroeconomic risk; fiscal policy rules; monetary unions; macroeconomic stability